2013
DOI: 10.1517/14712598.2013.795942
|View full text |Cite|
|
Sign up to set email alerts
|

Educational session as a tool to increase patient satisfaction of switching etanercept from the prefilled syringe to the autoinjection pen

Abstract: The autoinjection pen is an advantageous delivery option for etanercept. This study provides further evidence to support that the education strategy is a valid method for switching anti-TNF-α drugs from syringe to pen in patients with rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…For instance, RA patients administering methotrexate with an AI experience less pain and prefer it over the PFS [21,22]. Selfinjection by AI is also preferred by patients using adalimumab [23,24], etanercept [25][26][27], and golimumab [28,29], as well as in other disease areas, such as diabetes and growth hormone deficiency [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RA patients administering methotrexate with an AI experience less pain and prefer it over the PFS [21,22]. Selfinjection by AI is also preferred by patients using adalimumab [23,24], etanercept [25][26][27], and golimumab [28,29], as well as in other disease areas, such as diabetes and growth hormone deficiency [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Several commercial subcutaneous products up to 1 mL are available, including Enbrel (Amgen, Thousand Oaks, CA), Humira (AbbVie, North Chicago, IL), Simponi (Janssen Biotech, Horsham, PA), and Stelaris (Janssen Biotech). [5][6][7][8][9] When the therapeutic dose can be formulated in 1 mL, prefilled syringes and autoinjectors typically serve as the preferred delivery systems for subcutaneous selfadministration. 6,10 To limit the injection volume to 1 mL, monoclonal antibody formulations often need to be formulated at high concentrations at !100 mg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Switching from a prefilled syringe to an auto-injector was associated with improved treatment compliance and persistence; patients with chronic diseases reported that auto-injection devices were preferable over prefilled syringes because they were less painful and simpler to use [ 74 , 76 , 77 ]. In one study, a 30% increase was observed in the number of patients self-administrating medication after switching to an auto-injector, which in turn led to a decrease in the proportion of patients requiring outpatient visits or additional assistance [ 76 ].…”
Section: Resultsmentioning
confidence: 99%